Improvement proposal for the coffee supply chain to increase exports: sector analysis in the Cajamarca region - Molina Buenaño, Daniela (2024)
This paper examines the coffee supply chain in Jaen and San Ignacio (Cajamarca, Peru) to propose enhancements to increase the volume of produce destined for exportation. The study of the coffee sector had an explanatory scope and a descriptive non-experimental design focused on the research variables of supply chain and exportation. It used a qualitative approach that combined interviewing a convenience sample and a literature review to investigate supply chain dynamics and exportation. Findings reveal challenges within the chain, including insufficient participation of coffee growers in cooperatives, limited financing, input scarcity, and inadequate technological adoption. Proposed solutions entail implementing the Internet of Things (IoT) and involving new stakeholders alongside a redesigned supply chain to augment production and facilitate greater export output.